EVALUATION OF CROSS TRANSPORT SUBSIDIES (Case Study Balikpapan - Taipa Route) (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Balikpapan - Taipa route, is one only one path contained in Kariangau port is still in subsidies. Which connects the city of Balikpapan (East Kalimantan) with Palu (Central Sulawesi) is within 204 miles with a long travel time during the 22 hours stipulated by the Minister Regulation No. 82 Year 1998 concerning Establishment of Inter-Provincial of ferry route. The route has a tendency to be a commercial track as seen from the data Productivity Passengers and vehicles continues to increase, so it is necessary to review the feasibility of the subsidy. In reviewing the feasibility analysis of the subsidy, then used some of the analysis of ships load factor is over the last five years in Operating Costs and revenues ship operators. Based on the analysis that had been done, be concluded that the load factor of vessels in 2020 amounted to 34.01 %, vessel operating expenses per year is Rp. 12,208,090,000, - with revenue per year is Rp. 5.280.859.000,- . Thus it can be said that in the operation of the vessel crossing is still a loss. Based on user demand forecasting freight services, in 2026, a factor unloading of ships reach the break even point in number 66.33 %. So it can be estimated that in that year, the track Balikpapan - Taipa already a commercial route. Where in 2026 the operation of the KMP. Madani has gained the advantage and the route has been a commercial track.